Efficacy of Hypochlorite in Disinfesting Nonfungal Plant Pathogens in Agricultural and Horticultural Plant Production A Meta-Analysis - Copes, Warren E (Plant disease, 2021)
Bleach products containing hypochlorite are commonly used as disinfectants to eliminate nonfungal plant pathogens from production surfaces, tools, plant surfaces, irrigation water, and produce dump tanks. Although bleach products are useful, their effectiveness has been reported to vary under specific settings. A meta-analysis was conducted of 86 studies to assess the overall efficacy of hypochlorite against plant pathogenic bacteria, oomycetes, and viruses and to identify factors that explain differences in product efficacy. Hypochlorite resulted in a significant (P < 0.0001) reduction in disease intensity or propagule viability, with a mean Hedges' g standardized difference ([Formula: see text]) of 3.01, indicating that overall, hypochlorite treatments are highly effective. However, heterogeneity in g was significant (P < 0.0001) between studies, wherein 69.8% of the variance observed in g was attributed to true effects. Furthermore, an estimate of between-study variability was moderate (τ2 = 1.46). Random effects (REs) metaregression showed limited effects of moderator variables dosage, contact time, targeted material of treatment, and organism type on product efficacy when all organism types were considered together. Because subgroup [Formula: see text] was significantly higher (P = 0.0070) for oomycetes ([Formula: see text] = 3.30) than for bacteria ([Formula: see text] = 2.19), subsequent metaregressions were performed by organism type. For oomycetes, five RE metaregression models, each containing two moderators and their interaction, resulted in significant (P = 0.05) effects, where models with dosage and time, dosage and genus, time and genus, dosage and target, and time and target accounted for ≤50, 71, 57, 48, and 47%, respectively, of the variance in true effect sizes (R2) associated with [Formula: see text]. For viruses, only the RE metaregression model containing time and target and their interaction resulted in significant (P = 0.0435) effects accounting for 38% of the variance in true effect sizes associated with [Formula: see text]. None of the RE metaregression models for bacteria were significant, although they still accounted for ≤28% of the variance in true effect sizes associated with [Formula: see text]. These results show that although the current recommended rates for dosage and contact time for commercial bleach products are generally expected to result in effective disinfestation, the efficacy against nonfungal plant pathogens is expected to be influenced by the organism type and target being treated with hypochlorite